PENGARUH ISLAM PADA TAMBO DALAM NARASI SEJARAH ASAL MUASAL DAN TRANSFORMASI SOSIAL MASYARAKAT MINANGKABAU - Pratama, Fikri Surya; Yola, Nilma; Husni, Nurul Izzati (Tambo: Journal of Manuscript and Oral Tradition, 2023)
As a literary work of the Minangkabau people, Tambo is said to be historical literature. In content, this tambo does not explain the existence of King Adityawarman as part of Minangkabau history, and only highlights figures who are Muslim. This research aims to analyse the extent of Islamic influence in the tambo manuscript, with the primary source of the manuscript "Undang-Undang Minangkabau" collection of Surau Parak Laweh Pariangan. This research is qualitative research with a philological approach, and the analysis uses a historical content analysis approach. The results showed that the preaching movement of the Tareqat Syatariyah in the darek area was greatly affected by the Paderi movement. The Tarekat Syattriyah wrote tambo containing historical, issues of Minangkabau customs and culture that had been integrated with Islam. Tambo is not only seen as a literary work with historical content and customs, but also as a product of a political agenda.